2023
DOI: 10.3390/jcm12247619
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Outcomes of Cutaneous Squamous Cell Carcinoma in Solid Organ Transplant Recipients: A Retrospective Comparative Cohort Study

Rafael Salido-Vallejo,
Lourdes Escribano-Castillo,
Javier Antoñanzas
et al.

Abstract: Introduction: Cutaneous squamous cell carcinoma (cSCC) is the second most common cutaneous neoplasm, and its incidence is on the rise. While most cSCCs have an excellent prognosis, certain risk factors, especially immunosuppression, have been associated with higher rates of local recurrence (LR), metastasis, and poor prognosis. This study aims to assess the risk factors for LR and metastasis development in cSCC among solid organ transplant recipients (SOTRs) and compare these rates with those in immunocompeten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Special skin cancer patient populations, such as solid organ transplant recipients with cutaneous SCC, may need a more personalized approach to their management [ 32 ]. The retrospective cohort study by Salido-Vallejo et al observed that the prognosis of cutaneous SCC is more closely related to other tumor-dependent risk factors than the immunocompromised state [ 33 ]. The retrospective analysis by Kuzmanovszki et al revealed that elderly, polymorbid, and immunocompromised patients with cutaneous SCC can be effectively treated with anti-PD1 inhibitor cemiplimab [ 34 ].…”
mentioning
confidence: 99%
“…Special skin cancer patient populations, such as solid organ transplant recipients with cutaneous SCC, may need a more personalized approach to their management [ 32 ]. The retrospective cohort study by Salido-Vallejo et al observed that the prognosis of cutaneous SCC is more closely related to other tumor-dependent risk factors than the immunocompromised state [ 33 ]. The retrospective analysis by Kuzmanovszki et al revealed that elderly, polymorbid, and immunocompromised patients with cutaneous SCC can be effectively treated with anti-PD1 inhibitor cemiplimab [ 34 ].…”
mentioning
confidence: 99%